EVALUATION OF OPTIMAL ECONOMIC AND TECHNICAL INDICATORS FOR AGRICULTURE STOCK TRADING DECISION - Kuzman, Boris; Petković, Biljana; Petković, Dalibor (International Journal of Economic Practice and Policy, 2022)
The main goal of the research was to determine which indicators are the most impactful on the buy and sell triggers of stocks to maximize profits of the trade. The aim was to determine the agriculture stock price movements based on economic and technical indicators. The investors in the stock market want to maximize trade profits bybuying or selling the stocks. Technical and economic analyses are conducted to determine whether to sell or buy agriculture stocks. Since many factors could impact stocks profit decisions, it is essential to determine which parameter has more or less influence on the decision. For such a purpose adaptive neuro-fuzzy inference system (ANFIS) was used since the method is suitable for redundant and nonlinear data. Generally, technical indicators are more valuable and impactful for agricultural stock trading decision-making. Technical indicator moving average convergence and divergence (MACD) strongly influences the stock trading decision. Economic indicatorrelative change after smoothing 15 days federal rate has the most decisive influence on the stock trading decision.
Keywords: stock profit; trading; decision; ANFIS; agriculture